The Influence of Promotion, Price Perception, Convenience and Trust on Food and Beverage Purchasing Decisions Using Gofood Features (Gojek Application Study in West Jakarta) - Hareka, Muhammad Bimo; Harwani, Yuli (Dinasti Publisher, 2025)
The development of technology is currently experiencing very tight competition, especially in the world of transportation and one of them is in Indonesia which experiences quite significant transportation developments every year. This study aims to determine